Improving Students’ Writing Ability Through Mobile-Assisted Language Learning (Mall) at STIT Palapa Nusantara Lombok-NTB: Meningkatkan Kemampuan Menulis Siswa Melalui Pembelajaran Bahasa Berbantuan Mobile (MALL) di STIT Palapa Nusantara Lombok-NTB - Rijnan (Al-Gafari : Manajemen dan Pendidikan, 2025)
This research investigated the utilization of mobile-assisted language to enhance students' writing skills. Conducting of the research was to improve student achievement in writing skills. This research was a classroom action research. The subjects were eighth-grade students in the High School of STIT Palapa. The procedure of the study consisted of two phases, namely the preliminary study and the action. In the preliminary study, information obtained was on the student’s problems, and in the action, the phases of action research presented in the classroom. Data collected were through observation, questionnaires, tests, and field notes. The data analyzed were quantitatively and qualitatively. The research result showed that using mobile support in language learning significantly improved students' writing skills. Before the implementation of the intervention, the mean score of students' writing achievement was 56; after the intervention, it was 78. The post-intervention score was higher than the pre-intervention score where the upper minimum completion criterion (KKM) for proficiency was 70 achieved by 25 students. The post-action success of MALL supported by several pieces of evidence were first, the use of MALL, students were motivated to learn English writing according to a lesson plan. Second, students focused on paying attention to the teacher's guide. Lastly, the material of the recount text designed was the juxtaposed pictures so that students found the idea of writing easily